Therapeutic role of extracellular vesicles from human umbilical cord mesenchymal stem cells and their wide therapeutic implications in inflammatory bowel disease and other inflammatory disorder - Din, Muhammad Azhar Ud; Wan, Aijun; Chu, Ying; Zhou, Jing; Yan, Yongmin; Xu, Zhiliang (Frontiers in Medicine, 2024)
The chronic immune-mediated inflammatory condition known as inflammatory bowel disease (IBD) significantly affects the gastrointestinal system. While the precise etiology of IBD remains elusive, extensive research suggests that a range of pathophysiological pathways and immunopathological mechanisms may significantly contribute as potential factors. Mesenchymal stem cells (MSCs) have shown significant potential in the development of novel therapeutic approaches for various medical conditions. However, some MSCs have been found to exhibit tumorigenic characteristics, which limit their potential for medical treatments. The extracellular vesicles (EVs), paracrine factors play a crucial role in the therapeutic benefits conferred by MSCs. The EVs consist of proteins, microRNAs, and lipids, and are instrumental in facilitating intercellular communication. Due to the ease of maintenance, and decreased immunogenicity, tumorigenicity the EVs have become a new and exciting option for whole cell treatment. This review comprehensively assesses recent preclinical research on human umbilical cord mesenchymal stem cell (hUC-MSC)-derived EVs as a potential IBD therapy. It comprehensively addresses key aspects of various conditions, including diabetes, cancer, dermal injuries, neurological disorders, cardiovascular issues, liver and kidney diseases, and bone-related afflictions.